160 Treatment and Comorbidities of Patients with Erectile Dysfunction Before and During COVID-19 in the United States: A Real-World Data Analysis. (1st May 2022) - Goldstein, I.; Hassan, T.; Li, J.; Riad, M.; Vignesh, S.; Zou, K.
ABSTRACT: Introduction: Erectile dysfunction (ED) is usually a symptom of another medical condition. People with poor overall health are more likely to develop severe form of coronavirus disease 2019 (COVID-19) and may have unwanted symptoms such as ED. COVID-19-related stress, anxiety, and depression can also impact sexual health and possibly lead to ED. There are various treatment options for patients with ED. However, real-world evidence of the impact of COVID-19 on the treatment and comorbidities of patients with ED is limited. Objectives: To estimate the impact of COVID-19 on the treatment and comorbidities of patients with ED in the United States. Methods: This retrospective real-world data (RWD) analysis used the IQVIA PharMetrics® Plus claims database, which is a patient-Centric, closed claims database of fully adjudicated pharmacy, hospital and medical claims anonymized at the patient level, that captures the complete patient journey for all services billed to and covered by the patient's health plan. We compared the ED treatment and comorbidities in adult males aged 18+ years with ED in the same 3-month periods before (01March - 31May, 2019) and during (01March – 31May, 2020) the COVID-19 pandemic. ED treatment included any ED-related claims, prescriptions of any and individual phosphodiesterase-5 inhibitor (PDE5i) medications (avanafil, sildenafil, tadalafil and vardenafil). Results: See the table below for number of patients having ED-related claims, having any and individual PDE5i prescriptions, number of patients with COVID-19 diagnosis, and percentage of patients with each of the top 10 comorbidities, in the 3-month periods before and during COVID-19. Conclusions: RWD showed that ED-related claims significantly decreased during the COVID-19 pandemic, reflecting the pandemic's impact on ED patients' health. However, the use of PDE5i medications remained stable during the pandemic. Key comorbidities including hypertension, hyperlipidemia, type 2 diabetes mellitus, benign prostatic hyperplasia with lower urinary tract symptoms, testicular hypofunction, and malignant neoplasm of the prostate, during the pandemic, compared with pre-pandemic period, highlighted the impact of the pandemic on ED patients' health and need for managing their other comorbid chronic diseases. Disclosure: Work supported by industry: yes, by Viatris. A consultant, employee (part time or full time) or shareholder is among the authors (Viatris).